2017
DOI: 10.1098/rsta.2017.0093
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approximation and numerical simulations for periodic travelling water waves

Abstract: We present recent analytical and numerical results for two-dimensional periodic travelling water waves with constant vorticity. The analytical approach is based on novel asymptotic expansions. We obtain numerical results in two different ways: the first is based on the solution of a constrained optimization problem, and the second is realized as a numerical continuation algorithm. Both methods are applied on some examples of non-constant vorticity.This article is part of the theme issue 'Nonlinear water waves'. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…For the case of constant vorticity, it is known that when the vorticity is below a critical value , the stagnation point first appears at the bottom and at that stage numerical continuation breaks down (Ko & Strauss 2008 b ). However, Amann & Kalimeris (2018) and Kalimeris (2018) found that when but is very close to , the branch of the bifurcation diagram ( plot) has another part which is bounded below and above by two values of the bifurcation parameter . These bounds correspond to two different waves in flows with stagnation point at the bottom and at the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of constant vorticity, it is known that when the vorticity is below a critical value , the stagnation point first appears at the bottom and at that stage numerical continuation breaks down (Ko & Strauss 2008 b ). However, Amann & Kalimeris (2018) and Kalimeris (2018) found that when but is very close to , the branch of the bifurcation diagram ( plot) has another part which is bounded below and above by two values of the bifurcation parameter . These bounds correspond to two different waves in flows with stagnation point at the bottom and at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Amann & Kalimeris (2018) expanded upon the method of Ko & Strauss (2008 b ), by allowing non-uniform grid points and enabling the continuation with vorticity as a bifurcation parameter. Using the latter scheme they successfully discovered a new part of the bifurcation curve for some critical constant vorticity values (see also Kalimeris 2018). Furthermore, Constantin, Kalimeris & Scherzer (2015 b ) proposed a penalization method to solve for large-amplitude waves.…”
Section: Introductionmentioning
confidence: 99%
“…Some other explicit solutions have been presented in the literature, for example by Boulanger et al [2] and Daboussy et al [6] for the steady state. Following the methodology of Constantin and Strauss [3], Kalimeris [9] proposes an asymptotic expansion of the Euler system reducing the problem resolution to a cascade of ODEs. On the one hand, the result of Kalimeris is not reduced to flows without vorticity, on the other hand the proposed solutions -also exhibiting singularities of the free surface -are not analytical because obtained through an iterative numerical process.…”
Section: Introductionmentioning
confidence: 99%
“…The flow beneath water waves can be captured by different numerical strategies, as outlined above. The following articles [7][8][9][10][11][12][13][14][15][16] are of interest to the problems discussed here. As will be presented herein, we adopt a boundary integral formulation (through Green's third identity) as well as conformal mappings, in order to compute our features of interest with great precision.…”
Section: Introductionmentioning
confidence: 99%